Phase characterisation of metalenses - Zhao, Maoxiong (Light Sci Appl, 2021)
Metalenses have emerged as a new optical element or system in recent years, showing superior performance and abundant applications. However, the phase distribution of a metalens has not been measured directly up to now, hindering further quantitative evaluation of its performance. We have developed an interferometric imaging phase measurement system to measure the phase distribution of a metalens by taking only one photo of the interference pattern. Based on the measured phase distribution, we analyse the negative chromatic aberration effect of monochromatic metalenses and propose a feature size of metalenses. Different sensitivities of the phase response to wavelength between the Pancharatnam-Berry phase-based metalens and propagation phase-reliant metalens are directly observed in the experiment. Furthermore, through phase distribution analysis, it is found that the distance between the measured metalens and the brightest spot of focusing will deviate from the focal length when the metalens has a low nominal numerical aperture, even though the metalens is ideal without any fabrication error. We also use the measured phase distribution to quantitatively characterise the imaging performance of the metalens. Our phase measurement system will help not only designers optimise the designs of metalenses but also fabricants distinguish defects to improve the fabrication process, which will pave the way for metalenses in industrial applications.